2013
DOI: 10.1016/j.fob.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine enhances NGF‐induced MAPK and Akt signals through the extracellular domain of TrkA in PC12 cells

Abstract: Lysophosphatidylcholine (LPC) is one of the major lysophospholipids mainly generated by phospholipase A2 (PLA2)-mediated hydrolysis of phosphatidylcholine (PC). We previously found that LPC displays neurotrophin-like activity in the rat pheochromocytoma PC12 cells and in cerebellar granule neurons, but the molecular mechanism remains unclear. We report here that LPC specifically enhances nerve growth factor (NGF)-induced signals in PC12 cells. When PC12 cells were treated with NGF, MAPK was phosphorylated, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…The decreased levels of LPCs were associated with an activated inflammatory status in cancer patients [34]. LPCs not only have inflammatory activities, but also activate signaling molecules including tyrosine kinases [3537]. The binding of LPCs to their receptors may regulate signaling pathways including inflammation and cell migration [35, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased levels of LPCs were associated with an activated inflammatory status in cancer patients [34]. LPCs not only have inflammatory activities, but also activate signaling molecules including tyrosine kinases [3537]. The binding of LPCs to their receptors may regulate signaling pathways including inflammation and cell migration [35, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt pathway is particularly important for mediating neuron survival under a wide variety of circumstances. Activation of the PI3K/Akt pathways is essential for neurotrophin-mediated survival; knockdown of Akt expression impairs NGF-and BDNF-mediated H19-7 hippocampal progenitor cell and primary hippocampal neuron survival [39]. Moreover, as the downstream signal of PI3K/Akt, GSK-3β also plays an important role in cell death [40].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that increased endogenous neurotrophic factors, such as brain-derived neurotrophic factor (BDNF), can activate various intracellular signaling pathways including ERK signalings (Choi et al, 2008; Wuhanqimuge et al, 2013). BDNF may interact with other signaling pathways and co-regulate cellular functions including survival, differentiation, and metabolism (Mendoza et al, 2011; Yun et al, 2005).…”
Section: Introductionmentioning
confidence: 99%